2014
DOI: 10.1158/0008-5472.can-14-0459
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length in White Blood Cell DNA and Lung Cancer: A Pooled Analysis of Three Prospective Cohorts

Abstract: We investigated the relationship between telomere length and lung cancer in a pooled analysis from three prospective cohort studies: the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial, conducted among men and women in the United States, and previously published data from the Alpha-Tocopherol, Beta-Carotene Cancer Prevention (ATBC) trial conducted among male smokers in Finland, and the Shanghai Women's Health Study (SWHS), which is comprised primarily of never-smokers. The pooled populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
92
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 41 publications
(43 reference statements)
14
92
4
Order By: Relevance
“…39 However, based on prospective studies, a consensus is now building that major cancers (including sporadic melanoma, adenocarcinoma of the lung, and cancers of the breast, pancreas, and prostate) are associated with an inherently longer LTL. [11][12][13][14][15] Our results suggest that the propensity to major cancers associated with long LTL might already be present at birth.…”
Section: Figurementioning
confidence: 60%
See 1 more Smart Citation
“…39 However, based on prospective studies, a consensus is now building that major cancers (including sporadic melanoma, adenocarcinoma of the lung, and cancers of the breast, pancreas, and prostate) are associated with an inherently longer LTL. [11][12][13][14][15] Our results suggest that the propensity to major cancers associated with long LTL might already be present at birth.…”
Section: Figurementioning
confidence: 60%
“…The ramifications of LTL dynamics for human health are an area of active research. Although short LTL is associated with increased risk of atherosclerotic cardiovascular disease [5][6][7] and diminished longevity, [8][9][10] long LTL is associated with major cancers, including melanoma, 11 adenocarcinoma of the lung, 12 cancers of the breast 13 and pancreas, 14 and aggressive cancer of the prostate. 15 LTL research has been predominantly performed in adults.…”
mentioning
confidence: 99%
“…44 This is further supported by an independent study that demonstrated a pronounced association between telomere length and lung cancer risk in female adenocarcinoma cases. 45 Longer telomeres in females were reported in several other studies including a recent meta-analysis. 46-48 Estrogen may explain gender difference with respect to telomere length.…”
Section: Discussionmentioning
confidence: 70%
“…In some types of cancers, such as gastric and bladder cancer, shorter RTL in leukocytes was a risk factor of tumorigenesis, [12,13,21] while it was opposite in lung and colorectal cancer. [17,18] …”
Section: Discussionmentioning
confidence: 99%